In vitro formation of adventitious shoots on caulinary tissue of physiologically contrasting Agave angustifolia plants - Rodriguez-Ortiz, Suzel Rios-Ramirez; Luna, Judith Ruiz-; Velasco, Vicente Arturo Velasco- (Emirates Journal of Food and Agriculture, 2018)
To micropropagate agave plants, somatic tissue is obtained from selected plants that are conditioned for 2 to 6 months to improve their physiological condition and health before in vitro cultivation. The objective of this study was to evaluate the physiological condition of Agave angustifolia plants in terms of its effect on organogenic response in somatic tissue taken from these plants when they are established in similar culture media. In a nursery, growth of four groups of plants was evaluated when they were subjected to different types of irrigation for seven months: 1) water; 2) NS-50% (fertigation with nutrient solution at 50% strength); 3) NS-75%; and 4) NS-100%. At the end of the period, it was found that supplying nutrients is important for plants to achieve better physiological condition. The unfertilized plants and those that received NS-75% had increases of 3.8 and 7.8 leaves, 6.5 and 12.5 cm in length of the largest leaf, and 1610.3 and 4401.4 cm2 in leaf area. Stem tissue was obtained from these stock plants and cultured for 90 days in in vitro culture, and formation of adventitious shoots was assessed. The results showed that the magnitude of organogenesis in stem tissue for formation of adventitious shoots was positively related to the physiological condition of the stock plant. Explants taken from unfertilized stock plants formed 14.6 total shoots and 3.8 shoots on each explant, while those fertigated at 100% concentration of nutrients formed 32.7 total shoots and 8 shoots on each explant.